24 GHz Short Range Radar System Measurements for Synthetic Aperture Radar Imaging - Caliskan, Alper; Yamac, Yunus Emre; Uysal, Husamettin; Turk, Ahmet Serdar; Kizilay, Ahmet; Orhan, Melek (IEEE, 2017)
In this paper, 24 GHz short-range radar measurements and synthetic aperture radar (SAR) imaging results are presented. The designed radar system has one transmitter and one receiver channel and 24 GHz output carrier signal is modulated with 50 MHz square wave at the transmitter channel. In the measurement, horn antennas are used for synthetic radar imaging and A-scan data were obtained with 90 m range. We applied SAR imaging algorithm in order to improve the image resolution to raw B-scan data. Raw and processed data are demonstrated comparatively for target detection performance.
Keywords: millimeter wave; short-range radar; synthetic aperture radar imaging; Engineering; Remote Sensing; Telecommunications